Hospitalization Services Utilization Between Permanent and Migrant Females in Underdeveloped Rural Regions and Contributing Factors—A Five-Time Data Collection and Analysis - Wen, Xiaotong; Zheng, Huilie; Feng, Zhenyi; Tucker, Winter; Lu, Yuanan; Yuan, Zhaokang (International journal of environmental research and public health, 2019)
The proportion of migrating females has increased, and more often, old females are left in rural regions. Resources are needed to provide suitable hospitalization service to females in underdeveloped rural regions. Using multi-stage hierarchical cluster random sampling method, nine towns from three counties were enrolled in five-time points between 2006 and 2014 in this study. The research subjects of this study were females age 15 and up. Data regarding the utilization of inpatient services were collected and analyzed. Complex sampling logistic regression was conducted to analyze influencing factors. This study reveals that for both permanent females and migrant females, the older their age, the higher their hospitalization rate. The utilization of hospitalization service for permanent females was associated with the occurrence of chronic diseases (adjusted Odds Ratio (aOR) = 5.402). In addition, permanent females suffering from chronic diseases were more likely to avoid hospitalization despite their doctor’s advice (aOR = 34.657) or leave the hospital early against medical advice (AMA) (aOR = 10.009). Interventions to combat chronic diseases and adjust compensation schemes for permanent females need to be provided.